Influence of DOM and its subfractions on the mobilization of heavy metals in rhizosphere soil solution - Meihua Lian; Jun Wang; Yangyang Ma; Jiahui Li; Xiangfeng Zeng (Scientific Reports, 2022)
Abstract Long-term industrial pollution, wastewater irrigation, and fertilizer application are known factors that can contribute to the contamination of heavy metals (HMs) in agricultural soil. In addition, dissolved organic matter (DOM) plays key roles in the migration and fate of HMs in soil. This study investigated the effects of amending exogenous DOM extracted from chicken manure (DOMc), humus soil (DOMs), rice husk (DOMr), and its sub-fractions on the mobilization and bio-uptake of Cd, Zn, and Pb. The results suggested that the exogenous DOM facilitate the dissolution of HMs in rhizosphere soil, and the maximum solubility of Zn, Cd, and Pb were 1264.5, 121.3, and 215.7 μg L−1, respectively. Moreover, the proportion of Zn-DOM and Cd-DOM increased as the DOM concentration increased, and the highest proportions were 97.5% and 86.9%. However, the proportion of Pb-DOM was stable at > 99% in all treatments. In addition, the proportion of hydrophilic acid (Hy) and Pb/Cd in the rhizosphere soil solution were 17.5% and 8.3%, respectively. This finding suggested that the Hy-metals complex has a vital influence on the mobilization of metals, besides its complexation with fulvic acid and humic acid. Furthermore, the elevated DOM addition contributed to an increment of HMs uptake by Sedum alfredii, in the following order, DOMc > DOMs > DOMr. This study can provide valuable insights to enhance the development of phytoremediation technologies and farmland manipulation. Since the risk that exogenous DOM would increase the uptake of HMs by crops, it is also needed to evaluate this case from an agricultural management perspective.